Analysis and reformulation of the knowledge organization of Communication field: application for UNESCO code - Marzal Felici, Javier; García Jiménez, Antonio; Humanes, María Luisa (Revista General de Información y Documentación, 2016)
The organization and codification of the field of Communication Sciences is studied, mainly in regard to UNESCO codes. The objective is to propose a change in these codes, because the classification and organization method of a scientific discipline has operational and epistemological consequences in the academic work. In this paper the current classification is presented, which shows a limited and scattered presence of terms related to Communication. Practical and theoretical difficulties of its reorganization, possible sources (curricula, conferences, scientific journals, documentary proposals, keywords) and work methods are described, considering two theoretical bases: Knowledge Organization and Communication. Finally, two different disciplines (History of Communication and Communication Technologies) are analysed through the information collected in a database, which includes subjects of Bachelor and Master degrees in 12 Spanish universities. It is also noted that this kind of proposal requires knowledge derived from documentary instruments such as classifications and thesauri.